THE EFFECTS STREET-NETWORK CONFIGURATION IN MODELLING WALKABILITY THROUGH SPACE SYNTAX - Nova Asriana; M. Donny Koerniawan; Lily Tambunan; Beta Paramita (DIMENSI (Journal of Architecture and Built Environment), 2023)
This study investigates street network connectivity in an informal settlement, Kampong Taman Sari, Bandung. It generally refers to the informal residential area with minimum facilities and urban services. The majority of these settlements depict irregular patterns and narrow paths or alleys. Thus, kampong inhabitants mainly rely on walking, biking, and riding motorcycles to access vital urban features and functions. This purpose study is to examine the potential connectivity not only for accessibility but also for evacuation movement in an informal settlement. This investigation also aims to understand an associative relation between street-network configuration and informal settlement patterns with the probability distribution of pedestrian movement. This study utilizes computational street network analysis through the space syntax method that consists of two distinctive evaluations, such as axial analysis and visual graph analysis. The following result depicts the spatial accessibility, integration, permeability, walkability, and connectivity based on this relation. Experimenting in modelling a walkable kampong in the urban environment will conduce to urban design qualities of the street environment and street network layout for pedestrians or users.